(untitled) (Journal of Engineering, 2014)
The permanent deformation of flexible pavement represent serious problem in hot climate region. Numerous efforts are devoted to mitigate this distress such as modifying asphalt binder by polymers. The present study demonstrate the effect of utilizing four types of polymers to reduce the permanent deformation, these polymers are Polyethylene Wax (PEW), Styrene Butadiene Rubber (SBR), Ethylene Propylene Dien Monomer (EPDM) and Ethylene Vinyl Acetate (EVA). The prepared mixtures composed of 4.9 % of 40/50 asphalt binder, 12.5 mm nominal aggregate maximum size and limestone dust as filler. The permanent and resilient strains have been recorded when the cylindrical specimens, 101.6 mm in diameter and 203.2 mm in height, tested by repeated loading system. The main conclusions exhibit that SBR and EPDM with the same concentration (15 % by weight of asphalt binder) reduced the permanent deformation by 30.20 % and 30.46 % respectively. Although, the PEW and EVA reduced permanent deformation by lower values, 13.24 % and 17.35 % respectively, but the incremental percentage of their action are higher. The influences of testing temperature and stress level on permanent deformation were investigated. Linear regression model was established to correlate the values of permanent deformation and the resilient modulus of asphalt mixtures.